Posibles efectos e impactos económicos para Colombia como consecuencia del Brexit (2019)
Explain the multiple possible economic scenes which could happen in Colombia as a consequence of the Brexit execution, taking into account the historical relationships between the two countries, analysing also the historical and actual situation of Brexit, and concluding with the principle objective to formulate the possible effects that Brexit could generate in Colombia.